“I’m afraid I can’t”: Initiating Acts on Refusal Strategy Realization - Dwiana, Nadya Rezkhita; Basthomi, Yazid; Anugerahwati, Mirjam; Syahri, Indawan (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
This study aimed to investigate how initiating acts affect refusal strategies realization. The subjects were 45 English Education Program students of Universitas Muhammadiyah Palembang. The study used Discourse Completion Task (DCT) which consisted of 12 situations covering four initiating acts; suggestion, request, offer, and invitations, and the classification of refusal strategy by Beebe et al was also used to categorize refusal strategies realized. The results showed that initiating acts were not insensitive towards the use of direct strategy. However, it has an impact on the realization of indirect strategies and adjuncts. It was also found that both initiating acts and the social status of interlocutors play an important role in producing refusal utterances. Hence, it is highly suggested to introduce initiating acts and social status factors to EFL learners so that they would be able to produce an appropriate refusal depending on the context.